2021
DOI: 10.1002/jemt.23861
|View full text |Cite
|
Sign up to set email alerts
|

Deep convolutional generative adversarial network for Alzheimer's disease classification using positron emission tomography (PET) and synthetic data augmentation

Abstract: With the evolution of deep learning technologies, computer vision-related tasks achieved tremendous success in the biomedical domain. For supervised deep learning training, we need a large number of labeled datasets. The task of achieving a large number of label dataset is a challenging. The availability of data makes it difficult to achieve and enhance an automated disease diagnosis model's performance. To synthesize data and improve the disease diagnosis model's accuracy, we proposed a novel approach for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 80 publications
(89 reference statements)
1
38
0
Order By: Relevance
“… Han et al (2021) reported the medical anomaly detection GAN (MAGAN) with an AUC of 0.89. Three studies showed higher accuracy of GAN-based methods (0.71, 0.85, and 0.83) ( Islam and Zhang, 2020 ; Shin et al, 2020 ; Sajjad et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… Han et al (2021) reported the medical anomaly detection GAN (MAGAN) with an AUC of 0.89. Three studies showed higher accuracy of GAN-based methods (0.71, 0.85, and 0.83) ( Islam and Zhang, 2020 ; Shin et al, 2020 ; Sajjad et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the publication year, all the included articles were published between 2018 and 2021, and more than half of them (8/14) were published in 2021 ( Figure 2A ; Baydargil et al, 2021 ; Gao et al, 2021 ; Han et al, 2021 ; Kang et al, 2021 ; Lin W. et al, 2021 ; Sajjad et al, 2021 ; Zhao et al, 2021 ; Zhou X. et al, 2021 ). Regarding the data source, neuroimaging data analyzed in 13 studies were mainly from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) ( Pan et al, 2018 ; Yan et al, 2018 ; Wegmayr et al, 2019 ; Islam and Zhang, 2020 ; Kim et al, 2020 ; Shin et al, 2020 ; Baydargil et al, 2021 ; Gao et al, 2021 ; Kang et al, 2021 ; Lin W. et al, 2021 ; Sajjad et al, 2021 ; Zhao et al, 2021 ; Zhou X. et al, 2021 ), and some data were from the Open Access Series of Imaging Studies (OASIS) ( Han et al, 2021 ; Zhao et al, 2021 ), the Australian Imaging, Biomarker and Lifestyle Flagship Study of Aging (AIBL) and the National Alzheimer’s Coordinating Center (NACC) databases ( Figure 2B ; Zhou X. et al, 2021 ). Two studies established a test set from the collection of clinical data ( Wegmayr et al, 2019 ; Kim et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations